Neglected tropical diseases: less known subjects amongst health care professionals - Wilson Karoke (Berita Kedokteran Masyarakat (BKM), 2018)
Wilson Karoke expressed concern about the low priority the governments in developing countries paid to common tropical diseases. They have limited funding for research and for programs to address the problem. Even more sadly, health workers get less exposure to information on research and discussion  on diseases considered as which can further make the problem neglected.